OFFENCE OF FRAUDULENT MANAGEMENT - ION CRISTINEL RUJAN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2014)
The activity of the directors of companies and the activity of others who are required to manage the assets of individuals or legal entities - public or private, as well as people who have special skills in relation to these legal entities must be conducted in compliance with the legal provisions incidental to heritage management . It is important that the manager of the company should not confuse the company patrimony with his own patrimony so as to be detrimental to the legal person and legal administrators , liquidators or their representatives or agents should not enter into legal acts detrimental to the person whose heritage he manages under special procedures provided by law. From the perspective of the legal protection of corporate assets and individuals, along with other legal provisions of special laws and other offenses relating to the protection of goods, fraudulent management is distinguished as a specific offense to be retained when the perpetrator inflicts an injury to a person , during the administration or preservation of its assets, although he had to take care of the administration or preservation of those goods. Fraudulent management also exists if the offense is committed by the legal administrator , the liquidator of the debtor’s fortune or a representative or his agent.